Medication use and deprescribing in older patients in the last 14 days of life. (26th March 2021) - Alwidyan, T; McCorry, N; Black, C; McConnell, T; Coulter, R; Forbes, J; Parsons, C
Abstract: Introduction: Older patients may continue to receive potential inappropriate medications (PIMs) at the end of life. Application of consensus-based tools to identify PIMs may result in the identification of candidate medications for deprescribing, with the aim of overcoming the harm of inappropriate medication and improving clinical outcomes. This study aims to describe medication use and deprescribing patterns, and to assess prescribing appropriateness for older people in the last 14 days of life in the hospice setting. Methods: Longitudinal, retrospective cohort study of deceased patients (≥65 years) who died between 1 January 2018 and 31 December 2018 in three hospices in a region of the United Kingdom. We identified prescribed and deprescribed medications and assessed medication appropriateness using consensus-based criteria, namely STOPPFrail [1] and criteria developed by Morin et al. [2] Unexpected/sudden deaths were excluded. Statistical analysis was conducted using SPSS statistics 26.0. Preliminary results: Data collection is currently ongoing. To date, data from 69 deceased patients have been collected (mean age 76.1 years). Of these decedents, 62.3% were female and the majority (just under 90%) had cancer reported as the cause of death. During the last 14 days of life, each patient was prescribed a mean of 17 ± 5 different medications. The mean number of medications decreased significantly between day 14 and the day of death from 13.2 ± 4.4 to 9.4 ± 3.7 (P < 0.01). Six hundred and thirty-nine medications were discontinued, with just under 70% stopped in the last seven days before death. 34.9% of those discontinued were prescribed for chronic conditions and 22% were proton pump inhibitors. In most decedents, swallowing difficulty was the reason for medication discontinuation. According to the STOPPFrail criteria [1], 42 (60.1%) of decedents received at least one PIM between day 14 and the day of death. There were 59 PIMs in total for these patients; of these 20.3% were hyoscine butyl-bromide and 16.9% were gliclazide. Using the criteria developed by Morin et al [2], 103 medications were assessed as being of questionable (81.6%) or inadequate (18.4%) clinical benefit. Of these, 64.1% were initiated during hospice admission. There was a statistically significant association between medications of questionable clinical benefit and medication number during the last 14 days of life (P < 0.01). Three of the PIMs were vitamins, considered inappropriate by both sets of criteria. Prescribing of PIMs reduced as patients neared death. Conclusion: A substantial proportion of older patients with life-limiting diseases receive PIMs during their last days of life. No systematic discontinuation of inappropriate medications was observed thus guidelines and resources are needed to facilitate rationalisation and deprescribing of drug treatments for older patients in the last days of life. The small sample size makes the relationship between most variables insignificant; however, data extraction is still ongoing in hospices. References: 1. Lavan H, Gallagher P, Parsons C, Mahony O. STOPPFrail (Screening Tool of Older Persons' Prescriptions in Frail adults with a limited life expectancy): Consensus validation. Age and ageing. 2017; 46 (4): 600–607. 2. Morin L, Laroche M L, Vetrano D L, Fastbom J, Johnell K. Adequate, questionable, and inadequate drug prescribing for older adults at the end of life: A European expert consensus. European Journal of Clinical Pharmacology. 2018; 74(10): 1333–1342.